Determinants of postpartum depression among mothers in Debre Tabor town, North-central, Ethiopia: Community-based unmatched case-control study - Dagnaw, Fentaw Teshome; Addis, Wondimnew Desalegn; Tesfa, Desalegn; Desale, Aragaw Tesfaw; Issa, Nurayine Abubeker; Belachew, Yismaw Yimam; Yitbarek, Getachew Yideg; Belay, Alebachew Taye; Chanie, Ermias Sisay; Hailemeskel, Habtamu Shimels (Frontiers in Global Women's Health, 2022)
Background Postpartum depression (PPD) is a non-psychotic depressive disorder of variable severity, and it can begin as early as 2 weeks after delivery and can persist indefinitely if left untreated. In Ethiopia, the prevalence of postpartum depression is high. There is a dearth of literature to determine factors associated with postpartum depression in Ethiopia, specifically in the study area. Objective This study aimed to identify factors associated with postpartum depression among mothers in Debre Tabor Town, Northcentral Ethiopia. Method A community-based unmatched case-control study was conducted among mothers who were living in Debre Tabor Town and fulfilled the inclusion criteria. Postpartum mothers were selected using a simple random sampling technique from the listed sampling frame at the health center. Then, the sample cases and controls were interviewed until the sample size was fulfilled by using a consecutive sampling method. The data were entered into the EPI data version 4.6 and then imported and analyzed using SPSS version 25. Descriptive statistics of different variables were done by cross-tabulation. Binary logistic regression was used to assess the determinant factors with the outcome variable. A P-value of < 0.05 was considered to declare statistical significance. Results A total of 308 postnatal mothers living in Debre Tabor Town were included, with a 97.5% response rate. History of substance use in the previous 3 months (AOR: 6.47, 95% CI; 2.61, 15.74), current baby illness (AOR: 3.9, 95% CI; 1.5, 10.12), marital dissatisfaction (AOR: 2.41, 95% CI; 1.22, 4.75), unplanned current pregnancy (AOR: 3.46, 95% CI; 1.32, 9.12), and breastfeeding (AOR: 0.22, 95% CI; 0.09, 0.55) were independent factors that affected the occurrence of PPD. Conclusion This study revealed that a recent history of substance use (in the past 3 months), current baby illness, marital satisfaction, unplanned current pregnancy, and breastfeeding were associated with postpartum depression. Healthcare providers working in maternal and child health clinics and health extension workers should give special attention to postpartum mothers who have had a history of substance use, current baby illness, unplanned pregnancy, non-breastfeeding mothers, and mothers with poor marital satisfaction.